Suppression of Aspergillus fumigatus Germination by Neutrophils Is Enhanced by Endothelial-Derived CSF3 Production - Zhang, Wenxin; He, Dan; Wei, Yunyun; Shang, Shumi; Li, Dong; Wang, Li (Frontiers in Microbiology, 2022)
Infection with Aspergillus fumigatus can cause life-threatening diseases in immunocompromised patients with an unacceptable mortality rate. Angioinvasion is one of the features of severe invasive aspergillosis. Neutrophils are short-lived immune cells regulated by colony-stimulating factor 3 (CSF3) that play a key role in anti-fungal immune responses. To investigate the interactions between A. fumigatus and the host immune cells such as neutrophils, we stimulated human umbilical vein endothelial cells (HUVECs) with the conidia of A. fumigatus, and co-cultured them with human neutrophils. Apoptosis and functions of neutrophils were analysed. Our results showed that HUVECs up-regulate the expression of CSF3 which could reduce the apoptosis of neutrophils while enhancing their functions. Lack of CSF3 was associated with enhanced apoptosis of neutrophils with impaired function. This work indicated that the CSF3 is required for neutrophil survival and function, at least in the early stages of A. fumigatus infection.